An assessment on how the closure of mining industries has affected the development of small towns in Zimbabwe: a case Study of Shabanie Mine in Zvishavane - Zinyama, Rumbidzai Precious (Midlands State University, 2018)
The aim of this research was to assess how small mining towns in Zimbabwe have been affected by the closure of mining industries in terms of development using the case study of Shabanie mine in Zvishavane. In assessing the closure of mines, sustainable development was looked at to give the framework of what is expected in development as well as sustainable development goals. ZMDC was assessed in this research as it is the corporation that is in charge of maintaining and caring for the mines facing closure and closed. A number of aspects concerning the closure of mines were taken into considerations to the upbringing of this research. These are, importance of mining to development, negative effects of mining closure on development, indigenisation policy, reasons for the closure of Shabanie and the negative and positive reasons for the closure. Kamativi mine is briefly looked at to see what closure does to mine. Mines can close without warnings due to lack of markets and lack of machinery. However, mines should adopt the planning of mine closure as a necessary measure, avoiding a link with politics and making sure that worker welfare is maintained. The education of mine workers should be exercised for the establishment of an effective mining industry with productive skilled workers aiming at developing the area they operate in and Zimbabwe. The major research instruments used were interviews, questionnaires and structured observation. Descriptive methods were used namely qualitative approach and quantitative approach as the research design.